Математическое моделирование репродуктивной гибели облученых клеток эукариот - Книгавко, В. Г.; Пономаренко, Н. С.; Книгавко, Ю. В. (ХНУРЕ, 2008)
This work is devoted to mathematical simulation of processes which determine reproductive death of irradiated cells. The created model takes into consideration the phenomenon of saturation of repair system of DNA radiation damages and the structural- functional features of eukaryotic chromatin structure
Keywords: эукариот